DIETER GRIMM «VERFASSUNG UND PRIVATRECHT IM 19. JAHRHUNDERT. DIE FORMATIONSPHASE» (JUS PUBLICUM VOL. 269), MOHR SIEBECK, TÜBINGEN 2017, ISBN 978-3-16-155557-2 - KUMMER, JOACHIM (CODEX. Anuario de Ciencias Histórico-Jurídicas, 2021)
Dieter Grimm’s work has a history of its own: Finished in 1979 as his habilitation, it is the first part of a planned, but never realized, two-part series on the relationship between constitutional and private law. Only in 2017 Dieter Grimm decided to publish the first part. A second part, as he stated, will not be published. The book therefore is unfinished and already over forty years old which is even more impressive because it can still be considered a standard work on the history of constitutional and private law